The Use of Emojis in Language Communication on Social Media Platforms - Telaumbanua, Yasminar Amaerita; Telaumbanua, Nita Trima Niat; Halawa, Mercy Dwiyul; Gulo, Benedikta; Halawa, Dian Margaretha Enjelina; Waruwu, Elvi Krisnawati (Journal of English Language and Education, 2024)
Emojis have become crucial in digital communication, enhancing emotional expression and clarity on social media. However, discrepancies exist in how emojis are interpreted across different cultural and contextual settings. This study aims to explore emoji usage and interpretation among university students inEnglish Language Education Study Program at UniversitasNias. Employing a qualitative phenomenological approach, the research examines how emojis influence message meaning and clarity. Findings reveal that while emojis significantly enhance emotional nuance and expressiveness, their interpretation varies widely based on context and cultural background. This can lead to misunderstandings if emojis are not used appropriately. The study highlights the importance of understanding cultural and contextual nuances to ensure effective communication. Conclusively, while emojis enrich digital interactions, users must be mindful of their context-aware and culturally informed usage to maximize clarity and minimize misinterpretations.